Giulio Cesare Aranzio (Arantius) (1530-89) in the pageant of anatomy and surgery - (:unkn) unknown (My University, 2011)
Giulio Cesare Aranzio in Italian (Julius Caesar Arantius in Latin) has not received full acclaim for his achievements in the field of anatomy and surgery that remain unknown to most physicians. His anatomical books Observationes Anatomicas, and De Humano Foetu Opusculum and surgical books De Tumoribus Secundum Locos Affectos and Hippocratis librum de vulneribus capitis commentarius brevis printed in Latin and additional existing literature on Aranzio from medical history books and journals were analysed extensively. Aranzio became Professor of Anatomy and Surgery at the University of Bologna in 1556. He established anatomy as a distinguished branch of medicine for the first time in medical history. Aranzio combined anatomy with a description of pathological processes. He discovered the 'Nodules of Aranzio' in the semilunar valves of the heart. He gave the first description of the superior levator palpebral and the coracobrachialis muscles. Aranzio wrote on surgical techniques for a wide spectrum of conditions that range from hydrocephalus, nasal polyp, goitre and tumours to phimosis, ascites, haemorrhoids, anal abscess and fistulae, and much more. Aranzio had an extensive knowledge in surgery and anatomy based in part on the ancient Greek and his contemporaries in the 16th century but essentially on his personal experience and practice.